Shifting correlates of lizard thermal biology through space: the effect of climate and habitat on lizard body temperatures - Morley, Kate (2016)
With climate warming, many lizard species are at risk of extinction. This is largely due to low dispersal abilities, which may prevent range shifts to more thermally suitable environments, and due to low capacities of species to physiologically adapt to warmer temperatures. Therefore, understanding relationships between body temperatures and environmental variables, and how they vary with habitat, is key to understanding the relative vulnerability of species to climate change.